Delirium in geriatric patients with hip fracture - Konkayev , A.; Bekmagambetova, N.; Konkayeva, M.; Šerpytis , M.; Gineitytė-Ozolince, D.; Šipylaitė , J.; Jatužis , D. (Neurologijos seminarai, 2021)
ntroduction. Delirium occurs in up to 87% of the intensive care unit (ICU) patients and is associated with numerous poor outcomes. The drug most commonly used to treat delirium is haloperidol, a centrally acting dopamine antagonist. Dexmedetomidine, a selective alpha2-adrenergic agonist, is another promising agent for the treatment of ICU-associated delirium. The aim of this study was to evaluate the frequency and risk factors of delirium and the treatment efficacy of dexmedetomidine vs. haloperidol in elderly patients treated in ICU for hip fracture.Methods. The study included 207 geriatric patients hospitalized for hip fracture at the institute of Traumatology and orthopedics in Astana in 2017-2018 (data of 199 patients analyzed). The frequency and structure of delirium, as well as the efficacy of dexmedetomidine in the treatment of delirium compared with haloperidol, were evaluated. In the study, the patients were divided into 2 groups: a group of patients who developed delirium, and a control group. Subsequently, the patients with delirium were divided into two subgroups: subgroup D (dexmedetomidine subgroup) and subgroup H (haloperidol subgroup).Results. The prevalence of delirium among geriatric patients of orthopedic and traumatological profile was 78%. On the first day after surgery, delirium developed in 48% of patients, of whom half were diagnosed with a hypoactive form of delirium. The first signs of delirium were most common on the second day with a mean duration of delirium of 2 days. The Barthel index was 44.3±1.7 points in the delirium group and 70±2.3 points in the control group (p
Keywords: delirium; geriatric patients; hip fracture; dexmedetomidine